Historical origins of persistent inequality in Nigeria - Belinda Archibong (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Horizontal inequality by ethnic group has remained remarkably persistent for wealth, education, and access to certain services in Nigeria. While significant gains in the reduction of inequality and improvement in access have been made for more locally administered services, outcomes are stickier and largely divergent for wealth, education, and historically federally administered services like grid-based power access. Notable is the increasing or stagnant inequality of access to these measures in the northwest and northeast ethnic/geopolitical zones and a remarkable divergence for wealth outcomes for these two zones versus the rest of the country over the 1990-2013. This paper explores different explanations for the patterns observed and puts forth the thesis that persistent inequality in access to education and federally administered services is in large part driven by historical heterogeneous federal government policy towards different groups in Nigeria.
Keywords: O10; O43; O55; N27; 330; development; ethnicity; geopolitical zone; horizontal inequality; Nigeria